Belowground niche partitioning is maintained under extreme drought - Weides, Sophie E; Hájek, Tomáš; Liancourt, Pierre; Herberich, Maximiliane M; Kramp, Rosa E; Tomiolo, Sara; Pacheco-Riaño, L Camila; Tielbörger, Katja; Májeková, Maria (Ecology, 2024)
Belowground niche partitioning presents a key mechanism for maintaining species coexistence and diversity. Its importance is currently reinforced by climate change that alters soil hydrological conditions. However, experimental tests examining the magnitude of its change under climate change are scarce. We combined measurements of oxygen stable isotopes to infer plant water-uptake depths and extreme drought manipulation in grasslands. Belowground niche partitioning was evidenced by different water-uptake depths of co-occurring species under ambient and extreme drought conditions despite an increased overlap among species due to a shift to shallower soil layers under drought. A co-occurrence of contrasting strategies related to the change of species water-uptake depth distribution was likely to be key for species to maintain some extent of belowground niche partitioning and could contribute to stabilizing coexistence under drought. Our results suggest that belowground niche partitioning could mitigate negative effects on diversity imposed by extreme drought under future climate.
Keywords: období sucha; rostliny; water-uptake depth; Climate Change; Droughts; hydrological niche segregation; voda; climate change; belowground niche partitioning; Water; klimatické změny; rainout shelter; Plants; půda; extreme drought; pastviny; Grassland; grasslands; oxygen stable isotopes; Soil